Trade in secured debt, adjustment in haircuts and international portfolios - Tommaso Trani (Graduate Institute of International and Development Studies, 2011)
I study the composition of international portfolios under collateral constraints and the implied cross-border transmission of shocks. I develop an international portfolio model with these features, in which leveraged investors seek diversification in both assets and secured liabilities and in which the pledgeable portion of assets adjusts to the state of the economy, reflecting borrowers' credit risk. The new analytical results are as follows. First, agents choose endogenously how much to borrow from each country. Second, the collateral constraint, being a contractual link between secured and unsecured financial instruments, permits to compute portfolios without an arbitrage condition between those classes of assets. Finally, haircuts adjust endogenously through the change in the collateral values. After estimating the parameters governing this adjustment, I find that both portfolios and international transmission mechanism are quite sensitive to leveraged investors' funding. As for portfolios, secured bonds have particularly effective hedging properties in managing the terms of trade risk. As for the international transmission, tightening haircuts affect the economic slowdown: initially severe contractions are followed by quick reversions to the long-term equilibrium. On a cumulative basis, these two effects compensate if haircuts adjust precisely to the economic state. But in case of uncertainty about this adjustment, collateral constraints are a source of risk which cannot be internationally diversified.
Keywords: F32; F34; F41; G15; 330; financial flows; borrowing limits; creditworthiness; risk premia; international business; cycle; macroeconomic interdipendence